WIND ENERGY POTENTIAL IN YOBE, NORTHEASTERN NIGERIA: AN AIDED TECHNIQUE THROUGH GEOGRAPHIC INFORMATION SYSTEM AND REMOTE SENSING (FUDMA JOURNAL OF SCIENCES, 2022)
The role of wind energy and other renewable energy sources in combating climate change cannot be overemphasized. Many countries including Nigeria have so far implemented policy measures to promote renewable energy. Moreover, the most important step to be taken in order to effectively harness renewable energy is to estimate their potentials in terms of viability and sustainability. This study was focused on evaluate the wind energy potential zones in Yobe State, northeast Nigeria, using integrated multiple criteria decision-making analysis (MCDA), Geographical Information System and Remote Sensing (GIS-RS), and Analytic Hierarchy Process (AHP) methods. Weibull distribution statistical method was applied to validate the GIS-RS based analysis. The study revealed a wind speed variation ranged from 1.48 to 7.15 m/s and an average annual wind power density of about 80 W/m2. About 90 % of study area has about 90 % wind power density of about 85 W/m2 and below while the remaining 10 % is covered by wind power density ranged between 85 and 616.89 W/m2. The results of the study showed that the area is viable for wind power generation and distribution. Furthermore, the wind energy resource will yield favorable economic gain for the study area. Thus the study concluded that Yobe is a suitable area for wind power generation both at medium scale generation, and standalone connection system.
Keywords: Wind energy; Renewables; Geographic information system; Yobe; Remote sensing